Comprehensive Guide to Cloud Migration Strategy for Financial Systems - Sandeep Rachapudi (North American Journal of Engineering Research, 2021)
The paper aims to describe some of the common pitfalls that can be easily avoided during migration from on premises to cloud. The paper is not specific to any cloud technology or cloud survive provider, rather it addresses the common mistakes made and how they can be easily avoided. A financial system is taken into consideration to explain this topic, however the problems described, and the strategy described is generic in nature for any domain that uses IT systems.